Development of the first axillary in vitro shoot multiplication protocol for coconut palms - Wilms, Hannes; Bièvre, Dries de; Longin, Kevin; Swennen, Rony L.; Rhee, Juhee; Panis, Bartholomeus (Springer, 2021)
The coconut palm or “tree of life” is one of nature’s most useful plants and the demand for its fruit is increasing. However, coconut production is threatened by ageing plantations, pests and diseases. Currently, the palm is exclusively propagated via seeds, limiting the amount of planting material. A novel micropropagation method is presented, based on axillary shoot formation. Apical meristems of in vitro coconut seedlings are cultured onto Y3 medium containing 1 µM TDZ. This induces the apical meristem to proliferate through axillary shoots in ~ 27% of the initiated explants. These axillary shoots are seen as white clumps of proliferating tissue and can be multiplied at a large scale or regenerated into rooted in vitro plantlets. This innovative micropropagation method will enable the production of disease-free, high quality in vitro plantlets, which will solve the worldwide scarcity of coconut planting material.